2016
DOI: 10.1186/s12940-015-0080-1
|View full text |Cite
|
Sign up to set email alerts
|

Reporting back environmental exposure data and free choice learning

Abstract: Reporting data back to study participants is increasingly being integrated into exposure and biomonitoring studies. Informal science learning opportunities are valuable in environmental health literacy efforts and report back efforts are filling an important gap in these efforts. Using the University of Arizona’s Metals Exposure Study in Homes, this commentary reflects on how community-engaged exposure assessment studies, partnered with data report back efforts are providing a new informal education setting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…The natural interdependence of science literacy, health literacy, and environmental literacy have led to the evolution of current environmental health literacy (EHL) frameworks [8,9,10,11,12,13]. The Society for Public Health Education states that EHL “integrates concepts from both environmental literacy and health literacy to develop the wide range of skills and competencies that people need in order to seek out, comprehend, evaluate, and use environmental health information to make informed choices, reduce health risks, improve quality of life and protect the environment” [14].…”
Section: Introductionmentioning
confidence: 99%
“…The natural interdependence of science literacy, health literacy, and environmental literacy have led to the evolution of current environmental health literacy (EHL) frameworks [8,9,10,11,12,13]. The Society for Public Health Education states that EHL “integrates concepts from both environmental literacy and health literacy to develop the wide range of skills and competencies that people need in order to seek out, comprehend, evaluate, and use environmental health information to make informed choices, reduce health risks, improve quality of life and protect the environment” [14].…”
Section: Introductionmentioning
confidence: 99%
“…At its most fundamental level, EHL involves “an understanding of the connection between environmental exposures and human health” [ 24 ]. The definition of EHL is expanding from a quiescent, unidirectional model (knowledge acquisition) towards an action-based model that provides individuals and communities with the tools and information to understand their risks and to exert control over the environmental exposures that may lead to adverse health outcomes [ 24 , 25 ]. Reporting bio- and environmental monitoring data back to participants in environmental public health projects has proven to be a successful way in which to raise EHL.…”
Section: Introductionmentioning
confidence: 99%
“…Reporting bio- and environmental monitoring data back to participants in environmental public health projects has proven to be a successful way in which to raise EHL. The literature reveals that participants of biomonitoring studies with a report back effort: (1) generally want their results; (2) learn a great deal about environmental health when studies reported individual results along with comparative benchmarks and some sort of interpretive context; (3) understand results without undue alarm; (4) increase their understanding of the scientific method; (5) self-initiate new networking in resource-related issues; (6) began to consider possible exposure reduction strategies; and (7) leverage the report back results to inform government officials to be more stringent in their cleanup efforts [ 6 , 25 , 26 , 27 , 28 ]. Distinct frameworks have been used to evaluate the effectiveness of these reporting back efforts and they include clinical ethics and community-based participatory research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observed open data sharing act among participants served as an additional mechanism for relationship building and social participation in learning. Ample literature documents the importance of data report back in environmental health research (Brody et al 2014;Perovich et al 2018;Ramirez-Andreotta et al 2016;Vousden et al 2014). The benefits from data sharing events observed here suggest that designing for relationship building and social negotiation of knowledge can deepen participants' sense of connection to the project, the study purpose, and each other.…”
Section: Design For Relationship Buildingmentioning
confidence: 99%